international applications of US. Income taxlaw - Ernes R. Larkins, (John Wiley & Sons, Inc., 2004)
Library of Congress Cataloging-in-Publication Data: Larkins, Ernest R. (Ernest Radford) International applications of U.S. income tax law : inbound and outbound transactions / by Ernest R. Larkins. p. cm. Includes index. ISBN 0-471-46449-X (cloth : acid-free paper) 1. Income tax—United States—Foreign income. 2. Investments, Foreign—Taxation— Law and legislation—United States. 3. Aliens—Taxation—Law and legislation—United States. 4. Foreign tax credit—United States. 5. Double taxation—United States. I. Title: International applications of US income tax law. II. Title. KF6419.L37 2004 343.7305′248—dc21 2003014219 Printed in the United States of America 10 9 8 7 6 5 4 3 2 1 4133 P-00(FM) 9/11/03 2:27 PM Page iv My wife, Nancy, has acted as cheerleader (and unofficial press agent) throughout the process. She has my appreciation for her confidence and enthusiasm. I dedicate this text to the three people I have enjoyed teaching the most—my own children—Joshua, Esther, and Hannah. I also thank the many Georgia State University students who have taken my international tax class, and wish them well in their lives and careers.